Hellbox - Pronzini, Bill (Pronzini, Bill. "Nameless Detective" mysteries., 2012)
When his wife goes missing from their Sierra foothills cabin after spotting a suspicious man, the Nameless Detective and his associate, Jake Runyon, launch a search and rescue mission that stretches legal boundaries.